How can we reduce maternal mortality due to preeclampsia? The 4P rule - Henri Augusto Korkes; Ricardo Carvalho Cavalli; Leandro Gustavo De Oliveira; José Geraldo Lopes Ramos; Sérgio Hofmeister de Almeida Martins Costa; Francisco Lázaro Pereira de Sousa; Edson Vieira da Cunha Filho; Maria Rita de Souza Mesquita; Mário Dias Corrêa Júnior; Ana Cristina Pinheiro Fernandes Araújo; Alberto Carlos Moreno Zaconeta; Carlos Henrique Esteves Freire; et al. (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract In low and middle-income countries such as Brazil, most maternal deaths are related to hypertensive complications. Preeclampsia is the leading cause of maternal mortality and morbidity. Significant proportion is associated with the following factors: lack of identification of high-risk women, lack of adequate prevention, difficulty in maintaining a high-risk prenatal follow-up, delayed diagnosis, insecurity and low use of magnesium sulphate, delayed pregnancy interruption and lack of postpartum follow-up of these high-risk cases. Four major actions are proposed to minimize this alarming clinical picture and reduce the mortality rates due to preeclampsia, called the "4 P Rule" (Adequate Prevention - Vigilant Prenatal Care - Timely Delivery (Parturition) - Safe Postpartum). From this simple "rule" we can open a range of important processes and reminders that may help in the guidance of preeclampsia management.